Republic of Serbia : Financial Sector Assessment Program Update; Technical Note on Systemic Liquidity Management. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This Technical Note reviews Systemic Liquidity Management in Serbia. The liquidity management framework in Serbia, although generally efficient, is constrained by instability in the demand for excess reserves. The demand for excess reserves is generally a function of the quality of the systemic liquidity management by the central bank, the technical capability of commercial banks' treasurers to manage their balances adequately, and the overall efficiency of payment systems facilities for money market participants. The relatively high and unstable demand for excess reserves is therefore somewhat puzzling in Serbia.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet